Mimesis and/Is/as Restoration of Behaviour. Issue 1 (April 2022) - Deriu, Fabrizio
Abstract : In light of the paradigm shift which in Theatre Studies led to the emergence of a new (post)discipline that takes the notion of performance as its cornerstone, this essay discusses the productive convergence between mimesis and 'restored behaviour', namely the key process of every kind of performance in art, ritual, and ordinary life. This convergence can improve the understanding of the mimetic condition in the twenty-first century, provided we rely on a postmodern and, at the same time, pre-Platonic conception of mimesis. Even though 'restored behaviour' is not the same as mimesis, evidence for their proximity can be found in neuroscientist Merlin Donald's theory of the evolution of the human mind, in which he locates a pre-verbal stage named 'mimetic culture'. A final section draws some arguments from cognitive perspectives in evolutionary studies on literature in order to show how mimesis and performativity are likely to emerge as a pre-literary layer, confronting the present-day post-literary condition.